Mehanizmi družbene solidarnosti in rentniški kapitalizem - Breznik, Maja (Teorija in praksa, 2011)
On the basis of two examples, this article discusses the question of "total social exchange" as a combined system of commodity exchange and "gift-exchange": 1. public finances in renaissance Florence; and 2. the economy of copyright. The author analyses the perverse effect that emerges from the system of contemporary social solidarity: the pauperisation of society and rent-seeking capitalism.
Keywords: Blagovna menjava; Commodity exchange; Družbena menjava; Social exchange; Solidarity; Solidarnost; Kapitalizem; Capitalism; družbena solidarnost; menjava daru